2004
DOI: 10.1179/joc.2004.16.supplement-1.108
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Chemotherapy and Hematopoietic Progenitor Cell Transplantation for Breast Cancer

Abstract: Nowhere has there been more controversy in recent years than in the use of high dose chemotherapy (HDC) with autologous hematopoietic stem cell transplantation for breast cancer, both in the adjuvant setting and for advanced disease. Authors review and comment on the data from the studies so far reported and try to indicate what will be next in this field. They also discuss what may be the attitude to take in our everyday clinical practice, taking into account the availability of new chemotherapeutic agents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…16 In addition, because of the heterogeneity of intensity and duration of the standard dose chemotherapy (SDC) in the control arm, the outcomes of these studies have been quite variable. 17 As a contribution to the ongoing discussion on HDC for BC we report here the results of this therapeutic approach in almost 6000 women receiving ASCT at 370 European Group for Blood and Marrow Transplantation (EBMT) centers between 1990 and 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In addition, because of the heterogeneity of intensity and duration of the standard dose chemotherapy (SDC) in the control arm, the outcomes of these studies have been quite variable. 17 As a contribution to the ongoing discussion on HDC for BC we report here the results of this therapeutic approach in almost 6000 women receiving ASCT at 370 European Group for Blood and Marrow Transplantation (EBMT) centers between 1990 and 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Highs and lows in the enthusiasm for HDC in BC has been largely unreasonable since no definitive conclusions can be drawn despite a huge number of studies reported throughout the last two decades. 16,17 This has cast a pall over the entire field and has resulted in both a low accrual of early prospective trials (irrational exuberance phase) and a moratorium on new studies (reticence phase). The EBMT Registry data confirm that HDC with ASCT today is a safe procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The expanding indications of high‐dose therapy (HDT) in hematologic 1,2 and nonhematologic malignancies 3 are associated with an increasing request for simplification and cost reduction of routine freezing procedures.…”
mentioning
confidence: 99%
“…MITO-MEL schedule was the final part of two HDC programs (GOCAM RC study 1 and 2) ( Figure 1), including an induction phase with three courses of conventional chemotherapy with epirubicin (120 mg/m 2 ) and cyclophosphamide (600 mg/m 2 ) (EPI-CTX) ±three courses of docetaxel (100 mg/m 2 ) (DTX) and a first HDC consisting of cyclophosphamide (CTX) (6000 mg/m 2 ), thiotepa (THI) (500 mg/m 2 ) and carboplatin (CBP) (800 mg/m 2 ) or MEL (160 mg/m 2 ) plus THI (600 mg/m 2 ). PBSC were collected following the EPI-CTX chemotherapy.…”
Section: Patient Characteristics and Hdcmentioning
confidence: 99%